Formulation of a semi-defined medium for high cell density cultivation of Escherichia coli in shake flasks - Ng, Wenfa; Ting, Yen-Peng (PeerJ Preprints, 2016)
Microbes for environmental research should be cultured in growth media with characteristics (e.g., pH, ionic strength, and organic and ionic composition) as close to their original habitat as possible. In addition, the medium should also enable high cell density to be obtained - needed for providing sufficient cells in subsequent experiments. This in-progress report describes the formulation of a medium with an environmentally-relevant composition (i.e., lack of complex organics), and that allows aerobic high cell density cultivation of Escherichia coli DH5α (ATCC 53868) in shake flasks. The formulated medium comprises four components: a buffer system (K2HPO4: 12.54 g/L and KH2PO4: 2.31 g/L), vitamins (yeast extract: 12.0 g/L), salts (NaCl: 5.0 g/L and MgSO4: 0.24 g/L), and carbon and nitrogen sources (D-Glucose: 6.0 g/L and NH4Cl: 1.5 g/L). Notable characteristics of this medium were: high capacity phosphate buffer system (89 mM phosphate); 1:1 molar ratio between D-Glucose and NH4Cl; and yeast extract providing trace elements and a secondary carbon and nitrogen source. Growth experiments revealed that an OD600nm of 9 was obtained after 24 hours of cultivation at 37 oC. Glucose and NH4Cl served as primary carbon and nitrogen sources for this phase of growth. After 48 hours, the OD600nm reached 11, where carbohydrates, lipids and proteins in yeast extract provided the nutrients for biomass formation. Broth’s pH varied between 5.5 and 7.8 during cultivation, which was in the range conducive for E. coli growth. In comparison, the OD600nm of E. coli reached 1.4, 3.2, and 9.2 in three commonly used complex media; Nutrient Broth, LB Lennox, and Tryptic Soy Broth, respectively, over 48 hours under identical culture conditions. In addition, the formulated medium was able to maintain a large viable cell population for a longer period of time (three days) compared to Tryptic Soy Broth. Thus, preliminary data suggested that the formulated medium holds potential for use as a high cell density aerobic growth medium for Gram-negative bacteria.
Keywords: High cell density; Gram-negative; aerobic; shake flask; culture medium; bacteria